Smart al-Quran Reading Program with the Bil Hikmah Method to Improve the Quality of Students' Reading of the Al-Quran - Batula, Abu Warasy; Fakhruddin, Agus (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2024)
This community service activity was carried out on March 10-25 2024, which was attended by 20 participants who were members of the TPQ Husnul Khatimah Mosque, Bandung. This program was carried out based on partners' needs related to evaluating the implementation of the learning program, namely the lack of student attention to the quality of Al-Quran reading due to the weakness of the iqro method. To obtain maximum results, this program is carried out using a participatory method with a service learning model. This program runs well and smoothly in accordance with the stages outlined in the activity implementation schedule. This can be seen from the achievement of training objectives and the enthusiasm and activeness of participants in training activities. The results achieved through this program are very significant in increasing participants' knowledge and skills in reading the Al-Quran according to the rules of recitation, as well as increasing motivation in studying the Al-Quran by paying attention to the quality of Al-Quran reading.